Ganocochlearic acid A, a rearranged hexanorlanostane triterpenoid, and cytotoxic triterpenoids from the fruiting bodies of Ganoderma cochlear. Issue 115 (5th November 2015) - Peng, Xing-Rong; Wang, Xia; Zhou, Lin; Hou, Bo; Zuo, Zhi-Li; Qiu, Ming-Hua
Abstract : Ganocochlearic acid A (1 ) was a rearranged hexanorlanostane triterpenoid featuring a γ-lactone ring and a five-membered carbon ring. Compound4 exhibited relatively potent cytotoxic activity against MCF-7 cells (IC50 : 9.15 μM). Abstract : Ganocochlearic acid A (1 ), a rearranged hexanorlanostane triterpenoid featuring a γ-lactone ring and a five-membered carbon ring, and eleven new lanostane triterpenoids (2–12 ), along with six known analogues (13–18 ) were isolated from the fruiting bodies of Ganoderma cochlear . Their structures, including absolute configurations, were established on the basis of the MS, NMR, X-ray crystallographic, and ECD analysis. A plausible biosynthetic pathway for1 was proposed. Compounds7–9, 11–13 showed moderate cytotoxic activities against five human tumor cell lines (HL-60, SMMC-7721, A-549, MCF-7 and SW480) with IC50 values ranging from 8 to 30 μM. Compound4 exhibited relatively potent cytotoxic activity against MCF-7 cells (IC50 : 9.15 μM), compared to the positive control (cisplatin, IC50 : 12.7 μM).